GE_GERICHTE P/3525/2021 vom 27. März 2023 - GE Cour de justice (2023)
USAGE DE FAUX(DROIT PÉNAL);DISPOSITIONS PÉNALES DE LA LEI;ACQUITTEMENT;PRINCIPE DE LA BONNE FOI;INDEMNITÉ(EN GÉNÉRAL) | CP.251.al1; LEI.118.al1; LEI.115.al1.leta; LEI.115.al1.letb; LEI.115.al1.letc; CPP.22.al1; CPP.429.al1.leta